Impact of Artificial Intelligence Chatbots on Student Well-being and Mental Health: A Systematic Review - Sana Alsayed; Suha Khalil Assayed; Manar Alkhatib; Khaled Shaalan (People and Behavior Analysis, 2024)
Students in schools and colleges face some challenges, including rigorous academic schedules, academic work load, standardized tests, and assignments deadline, which can contribute to significant stress and mental health risks. Thus, numerous studies have been conducted to control stress between students, such as self-guided stress management programs. This paper reviews several studies published between 2019 and 2023 exploring the impacts of deploying state-of-the-art artificial intelligence chatbots which are used to boost and manage psychological disorders and mental health symptoms such as anxiety, depression, fear, and worry between prospective and current undergraduate students. This study outlines the key phases of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). It begins with screening (115) articles and subsequently includes (13) articles for intensive review, which all focus on psychological disorders and mental health conditions that can be influenced by the conversational agents and chatbots. However, the results revealed that anxiety and depression are the main psychological disorders that can be influenced by conversational agents and chatbots. Moreover, this review revealed multiple cases of universities and schools, emphasizing the implementation of chatbots for both learning and advising functions.  The Systematic Literature Review (SLR) in this study is constrained to the specific databases, and the search keywords were limited to the article title fields only; which excluded the abstracts. This could have caused some missing relevant studies. In future work, other essential databases will be included, such as Scopus and WoS. In addition, we will include more information about the technique and the complexities of using the chatbot as it may have a significant impact on student behaviors and emotions.